Polikotomi Pilihan Pengembangan Ekowisata Kawasan Borobudur - Amiluhur Soeroso (KINERJA, 2010)
Aim of the study is assessing consumer behavior of tourist who visits to Borobudur if an ecotourism concept will be used in this area. Data were obtained from participation of tourists in Borobudur temple and surrounding area of Jogjakarta municipality. Then, it was used polychotomous choice framework for finishing it.The results indicate that ecotourism concept able to properly apply. Then, education and income are becoming vehicle decision public policy for managing Borobudur area. Consumer knowledge about living environment more and more higher so that their activity choice is in green tourism products.  Consequently,  the survival  of  Borobudur  world  heritage  site  in  the  future  will  fully depend on its sustainable development policy.